The Influence of Public Perception on the Decision to Visit Cirebon City Tourist Destinations - Suryono, Chondro; Wachyudi, Sudiana (Jurnal Toursci, 2025)
Background. Cirebon City, one of the cultural heritage centers in the province of West Java, has various attractions, including natural, religious, community, culinary, and primarily cultural and historical tourism. For this reason, the quality of products and the quality of services provided by the Cirebon City Government play a crucial role in delivering views or perceptions for tourists, both before the tourists come to Cirebon City and after tourists enjoy and use the tourist objects and attractions in Cirebon City. In this case, the perception of tourist satisfaction with tourist objects and attractions in Cirebon City can be measured. Purpose. The purpose of this study is to find out the characteristics of domestic tourists who visit Cirebon City, to find out the perception of domestic tourists towards tourist attractions in Cirebon City, and to find out the influence of domestic tourist perceptions on the decision to visit tourist attractions in Cirebon City. Method. The data analysis method uses descriptive analysis and logistic regression. Descriptive analysis was carried out to examine tourists' profiles and characteristics, while logistic regression was used to examine the influence of tourists' perceptions related to tourism factors on the decision to visit tourist destinations. Conclusion. The factor that most influences the decision of tourists to return to travel to tourist destinations in Cirebon City is accessibility. The field that gets a perfect perception is the ease of getting transportation, but the problem of obstacles in the journey must still be considered, namely, congestion   Key words: Perception, Visitation Decisions, Tourist Destinations